Elevated Temperature Effects on Fly Ash-Based Geopolymer Composites Produced with Waste Granite Dust - Aygormez, Yurdakul (SPRINGER INT PUBL AG, 2022)
As the Ordinary Portland Cement (OPC) was found to be insufficient after high-temperature effects, alternative searches about geopolymers have gained speed today. The sources of geopolymers are waste products. Therefore, using different waste products in geopolymer production is the main purpose of this study. For this paper, fly ash-based geopolymer mortars were exposed to temperatures of 400, 700, and 1000 degrees C. After the high-temperature test, ultrasonic pulse velocity (UPV), compressive and flexural strength results were compared to the pre-test situation and the weight-loss results were found. As aggregate, waste granite dust (WGD) was used by substituting with Rilem sand up to 30%. A mixture of sodium hydroxide (NaOH) and sodium silicate (Na2SiO3) was used as an activator. Seven series were prepared with the control mix. For these seven series, sodium hydroxide was prepared as 10 M. In addition, two different molarities (6 M and 14 M) were used for the series that gave the highest result. The highest results were obtained using 20% WGD, and higher strength results were obtained as the molarity increased. When the strength and UPV results were examined, it was observed that they decreased with elevated temperatures. Visual inspection and scanning electron microscope (SEM) and X-ray powder diffraction (XRD) analyzes were also performed. After the visual inspection, the stability of the geopolymer samples was maintained despite the micro-cracks. As a result, while two different wastes such as WGD and fly ash were evaluated in this study, it has been supported that geopolymers are sustainable and promising products.
Keywords: Geopolymer; Fly ash; Rilem sand; Waste granite dust; High-temperature test; MECHANICAL-PROPERTIES; SILICA FUME; THERMAL-BEHAVIOR; TO-LIQUID; PERFORMANCE; METAKAOLIN; CEMENT; STRENGTH; RESISTANCE; CONCRETE; Engineering